Examining the Role of Aging Perceptions in Subjective Cognitive Decline. (21st October 2022) - Chapman, Silvia; Weiss, David; Broulíková, Hana M.; Sunderaraman, Preeti; Barker, Megan S.; Joyce, Jillian L.; Azar, Martina; McKeague, Ian; Kriesl, William C.; Cosentino, Stephanie
Abstract : Objective: While subjective cognitive decline (SCD) is gaining ground as a "preclinical" risk state for Alzheimer disease, its utility depends on our understanding of the factors linked to SCD. Rarely examined sociocultural factors including perceptions of aging may relate to the subjective experience of cognitive aging. Identifying such associations will help to refine the utility of SCD as an early marker of AD while setting the stage for addressing modifiable factors contributing to SCD. Methods: The study consisted of N=136 participants (68% female; 73% White; 22% Black race, agemean =74.72; educationmean =16.01). Questionnaires assessed SCD, depressive symptoms, and age perceptions (essentialist aging beliefs, subjective age, age group identification, and explicit/implicit age stereotypes). Cognitive functioning was measured with a semantic interference and learning task. Results: SCD was correlated with essentialist aging beliefs, age identification, and depressive symptoms [ r range =0.18 to 0.22, P range =0.009 to 0.02, confidence interval (CI)range =0.00-0.39]. Essentialist aging beliefs were correlated with subjective age and age group identification ( r range =0.22 to 0.42, P range <0.001 to 0.003, CIrange =0.08-0.57). Both age group identification and essentialism were correlated with depressive symptoms ( r range =0.22, P range =0.009 to 0.01, CIrange =0.04-0.39). In the adjusted regression model including depressive symptoms, age perceptions, and SCD, only SCD was associated with cognition ( b =−0.31, P <0.001). Conclusion: Although correlated with SCD, perceptions of aging do not explain the relationship between SCD and performance on a sensitive cognitive test among older adults.